Product Stability Education as an Effort to Introduce Pharmacy Among Students of MAN 6 Aceh Besar: Edukasi Stabilitas Produk sebagai Upaya Pengenalan Kefarmasian pada Siswa MAN 6 Aceh Besar - Elfa Yeni; Nurjannah; Hardiana (Akademi Farmasi YPPM Mandiri, 2026)
The lack of students’ understanding regarding proper medicine storage, expiration dates, and the scope of pharmacy professions remains a common issue in schools. This condition may affect adolescent health literacy and increase the risk of inappropriate medicine use. This community service activity aimed to improve students’ knowledge regarding pharmaceutical product stability while introducing the field of pharmacy to students of MAN 6 Aceh Besar. The implementation method used educational counseling through interactive lectures, discussions, question-and-answer sessions, and distribution of educational leaflets. The participants consisted of 60 twelfth-grade students who actively attended the program. The materials delivered included the concept of product stability, factors affecting drug quality, differences between expiration date and shelf life, and an introduction to pharmacy professions. The results showed an increase in students’ understanding of proper medicine storage and safe drug use. Participants also demonstrated high enthusiasm toward information related to pharmacy education and career opportunities. Overall, this activity was effective in improving health literacy while serving as a medium for introducing the pharmacy field to high school students.